2012
DOI: 10.1111/j.1651-2227.2012.02644.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular torsion: a 15‐year single‐centre clinical and histological analysis

Abstract: Chances of testicular salvage after torsion are higher if patients present early. The majority of patients presenting late (>6 h) require orchiectomy owing to testicular necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 31 publications
2
40
1
5
Order By: Relevance
“…1,5 However, there are only limited reports of early outcomes and re-presentation rates, particularly with comparison of conservative and operative management, with limited data on short-term morbidity associated with scrotal exploration. 3,[5][6][7][8][9][10] This study demonstrated a 10% re-presentation rate following initial management of the acute scrotum, with similar frequency of return in those managed conservatively and operatively at first presentation. Exploration rate on second presentation was notably higher in the subgroup of patients initially discharged without surgical intervention (71%).…”
Section: Discussionsupporting
confidence: 52%
“…1,5 However, there are only limited reports of early outcomes and re-presentation rates, particularly with comparison of conservative and operative management, with limited data on short-term morbidity associated with scrotal exploration. 3,[5][6][7][8][9][10] This study demonstrated a 10% re-presentation rate following initial management of the acute scrotum, with similar frequency of return in those managed conservatively and operatively at first presentation. Exploration rate on second presentation was notably higher in the subgroup of patients initially discharged without surgical intervention (71%).…”
Section: Discussionsupporting
confidence: 52%
“…The left testis is involved in 60-66% of cases. 244,245 On gross examination the testis is usually diffusely hemorrhagic and edematous. In a case where an intra-abdominal testis in a 3-month-old infant underwent torsion, the cut surface showed multiple cystic cavities, one to several centimeters in diameter, corresponding to areas of hemorrhagic necrosis of the parenchyma.…”
Section: Testicular Torsionmentioning
confidence: 99%
“…Timely restoration of blood flow is the most effective approach to save the ischemic testis (Ringdahl and Teague, 2006;Saxena et al, 2012). However, testicular torsion/restoration is a development process of ischemia-reperfusion injury, which can further aggravate the ischemic injury of the testis (Turner and Brown, 1993).…”
Section: Introductionmentioning
confidence: 99%